2007
DOI: 10.1021/jp076031z
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion in Nanoporous Phases:  Size Dependence and Levitation Effect

Abstract: Self-diffusivity, D, of diffusants in widely differing mediums such as liquids (e.g., solution), porous solids (e.g., guests in zeolites), or ions in polar solvents exhibit strong size dependence. We discuss the nature of the size dependence observed in these systems. Altogether, different theoretical approaches have been proposed to understand the nature of size dependence of D not only across these widely differing systems but even in just one medium or class of systems such as, for example, ions in polar so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
57
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 199 publications
6
57
0
Order By: Relevance
“…In our present system there is no domain formation and the intermittency is the effect of attractive solute-solvent interaction. While undergoing random walk, the solute explores the transient solvent cage 4,11 . As the solute is small when it passes through the neck of the cage it feels uneven attraction from the different solvent particles and spends longer time near a particular solvent, which can be envisaged as a sticky point and leads to the intermittency in the solute dynamics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our present system there is no domain formation and the intermittency is the effect of attractive solute-solvent interaction. While undergoing random walk, the solute explores the transient solvent cage 4,11 . As the solute is small when it passes through the neck of the cage it feels uneven attraction from the different solvent particles and spends longer time near a particular solvent, which can be envisaged as a sticky point and leads to the intermittency in the solute dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…Diffusion of smaller particles in a crowded medium is ubiquitous in nature and has huge industrial and academic relevance [1][2][3][4][5][6][7][8][9][10][11][12][13] . The diffusion of sodium chloride through granular soil bed is important in understanding the ground water contamination from solid waste landfills 14 .…”
Section: Introductionmentioning
confidence: 99%
“…This study is done in order to understand the non monotonic size dependence of diffusion of small solutes which was earlier found in simulation studies [9]. In the earlier simulation and experimental studies the diffusion of small solute particles in porous zeolite structures [13][17], pure solvents [9] and ionic medium [14] have predicted that the non monotonic size dependence of diffusion is a generic phenomena, independent of the nature of the solvent.…”
Section: Resultsmentioning
confidence: 87%
“…The solute tends to spend longer time bound to one side of the neck or one solvent particle (in case of LJ solvent), which leads to lower diffusion constant. In experiments, simulations and also in theoretical studies such maximum in diffusivity for ion diffusion in polar solvent has been found [12] [13][14][15][16] [17]. All these studies show that the non monotonic size dependence of diffusion is a generic phenomena independent of the nature of the solvent.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation